The Relationship between Transformational Leadership and Supply Chain Performance with Mediation Role of Job Satisfaction: Evidence from Egyptian Petrochemical Companies - Kamel, Mohamed; Ragheb, Mohamed A.; Salah, May; Farid, Shaymaa (The Arab Journal of Administration, 2024)
The purpose of this research is to empirically investigate the relationship between transformational leadership, job satisfaction, and supply chain performance in context of Egyptian Petrochemical Companies. The objectives of this research are: to investigate how transformational leadership affects Supply chain performance, to examine how transformational leadership Job satisfaction, to identify how Job satisfaction affects Supply chain performance, to investigate the mediation role of Job satisfaction between transformational leadership and Supply chain performance. The study followed the quantitative approach and data gathered from a survey of 466 acceptable responses. The results were analysed employing by structural equation model analyses (SEM) using AMOS software. The main conclusions drawn from this study are that, all the hypotheses are statistically supported. Finally, job satisfaction partially mediates the relationship between transformational leadership and Supply chain performance in the Egyptian petrochemical companies.